How We Came to Be : A Novel - Bernhard, Johnnie, 1962- (Book collections on Project MUSE., 2018)
"Fifty-year-old Karen Anders, a high school English teacher and the adoptive mother of Tiffany, comes to terms with being a single-parent and a clumsy drunk in the multicultural melting pot of Houston, Texas, as she forges an unlikely friendship with Leona Supak, a WWII Hungarian refugee, who inspires Karen to change her views on motherhood, drinking, and men. Karen's teaching job provides an ongoing challenge with low-scoring students and a lack of support from school administrators. Meanwhile, Tiffany moves to Austin to attend the University of Texas, but soon turns to drugs and a gamer boyfriend to try and cope when the stress of college life becomes too much. Tiffany hides the truth of her new life from Karen through a text-only relationship. Feeling rejected, Karen explores the paradox of romance for the middle-aged even as Tiffany's life going to pieces. In spite of the challenges, a family unit comes together inspired by strangers and disappointments in How We Came to Be"--Provided by publisher.